HUBUNGAN ANTARA DUKUNGAN SOSIAL DENGAN PENYESUAIAN DIRI PADA SANTRIWATI KELAS VII MTS DI PONDOK PESANTREN AL-FALAH - Muhamad Mursyid; Siti Fathiah Biongan (program studi psikologi, 2023)
This research aims to determine the relationship between social support and self-adjustment in female students of Class VII MTs at the Al-Falah Islamic Boarding School. This researchuses a quantitative research design with a population of 45 female students. The total sample was 45 female students using total sampling technique. The research results showed the level of social support for female students is in the medium categoryat 28 with 62.2%. Mean while female students' self-adjustment was in the medium category at 31 with 68.9%. Based on the results of the spearmenrank correlationtest with a correlationvalue (r) of 0.498 and a sig value (p) = 0.000 (p<0.05). Thus it can be concluded, thereis a positive relationship between social support and self adjustment in class VII MTs female students at the Al-Falah Islamic boarding school. This shows the higher social support, the better student's self-adjustment